Analisis Motivasi Kerja Sebagai Upaya Meningkatkan Kinerja Karyawan Pada Cafetranseat - Indira Yuana; Fauzih Fauzih; Pasrun Adam; Tania Regita (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Analysis of Work Motivation as an Effort to Improve Employee Performance at Café Transeat". Management Study Program 66 Kendari High School of Economics. Supervised by: Pasrun Adam as supervisor I and Indira Yuana as supervisor II. This study aims to find out and analyze: "how work motivation is given in an effort to improve employee performance at Café Transeat". The object of this research is the Analysis of Work Motivation as an Effort to Improve Employee Performance at Café Transeat. The informants of this study are cafe owners. To get an overview of the transeat café, it includes the profile and vision and mission of the café. And Café Treanseat employees. To obtain complete information about the conditions in Café Transeat. The information in this research is motivation and performance. Data analysis used descriptive qualitative. The results of this study concluded that Work motivation has an effect on increasing employee performance at Café Transeat.